Unattended automated office blood pressure measurement in children - Seeman, Tomáš; Staněk, Kryštof; Slížek, Jakub; Filipovský, Jan; Feber, Janusz (Blood pressure, 2021)
PURPOSE: We studied the performance of unattended automated office blood pressure (uAOBP) measurement in children, in relation to oscillometric office BP (OBP) and ambulatory blood pressure monitoring (ABPM). MATERIALS AND METHODS: One hundred and eleven stable treated and untreated outpatients investigated for hypertension underwent uAOBP measurements (seated unattended in a quiet room separate from the renal clinic room, six times after a 5 min rest with the BpTRU device), and immediately before using the oscillometric device. Ambulatory 24 h blood pressure monitoring (ABPM) was performed on the same day in a subgroup of 42 children. RESULTS: UAOBP measurements were successful in 106 children (95%), 5 pre-school children did not tolerate to be alone in the room. The mean ± SD systolic/diastolic uAOBP, OBP and daytime ABP were 109.1 ± 14.0/70.8 ± 10.7 mmHg, 121.6 ± 16.5/77.6 ± 10.5 mmHg and 123.5 ± 11.3/73.7 ± 6.8 mmHg, respectively. Systolic/diastolic uAOBP was significantly lower than OBP by 13.6/7.6 mmHg (p < 0.0001) and lower than daytime ABP by 14.4 ± 0.5/2.9 ± 0.3 mmHg (p < 0.0001). The heart rate was not significantly different during uAOBP than during OBP measurements. On Bland Altman analysis the uAOBP underestimated OBP by a mean of 15.6 mmHg for systolic BP and by 8.6 mmHg for diastolic BP. In all 9 children with white-coat systolic hypertension uAOBP was within the normal range (<95th pc for OBP), in six of nine children with white-coat diastolic hypertension uAOBP was within the normal range however, in three of them it was elevated despite normal ABP. CONCLUSION: uAOBP measurement is feasible in school-aged children, its values are considerably lower than OBP as well as daytime ABP and it could help with detection of white-coat systolic hypertension. The clinical applicability of uAOBP in children should be confirmed in further studies.
Keywords: syndrom bílého pláště; hypertenze; předškolní dítě; dítě; masked hypertension; White Coat Hypertension; lidé; Blood Pressure Monitoring, Ambulatory; Unattended automated office blood pressure; krevní tlak; Hypertension; children; Child, Preschool; Blood Pressure Determination; ambulantní monitorování krevního tlaku; white-coat hypertension; měření krevního tlaku; Child; Blood Pressure; Humans